The second summer of the Sisterhood - Brashares, Ann 1967- (Delacorte, 2003)
With a bit of last summer's sand in the pockets, the Traveling Pants and the Sisterhood that wears them embark on their 16th summer. Bridget: Impulsively sets off for Alabama, wanting to both confront her demons about her family and avoid them all at once. Lena: Spends a blissful week with Kostos, making the unexplainable silence that follows his visit even more painful. Carmen: Is concerned that her mother is making a fool of herself over a man. When she discovers that her mother borrowed the Pants to wear on a date, she's certain of it. Tibby: Not about to spend another summer working at Wallman's, she takes a film course only to find it's what happens off-camera that teaches her the most